Numeracy in early modern Korea, Japan, and China: The age-heaping approach - Baten, J.; Sohn, Kitae (2017)
© 2017 Elsevier B.V. This study first draws on a unique data set, hojok (household registers), to estimate numeracy levels in Korea from the period 1550–1630. We add evidence from Japan and China from the early modern period until 1800 to obtain human capital estimates for East Asia. We find that numeracy was high by global standards, even considering the potential sources of upward bias inherent in the data. Therefore, the unusually high level of numeracy in East Asia in the early 21st century was already present in the early modern period, with implications for our understanding of Asian growth processes.